2021
DOI: 10.1177/1049732320983270
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers’ Challenges to High-Quality HIV Care and Antiretroviral Treatment Retention in Rural South Africa

Abstract: Provision of high-quality HIV care is challenging, especially in rural primary care clinics in high HIV burden settings. We aimed to better understand the main challenges to quality HIV care provision and retention in antiretroviral treatment (ART) programs in rural South Africa from the health care providers’ perspective. We conducted semi-structured qualitative interviews with 23 providers from nine rural clinics. Using thematic and framework analysis, we found that providers and patients face a set of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Members of organizations are also more motivated when their environments are conducive to success ( Dekker, 2008 ; de Kok et al, 2020 ; Julien et al, 2021 ; Mathauer & Imhoff, 2006 ; Sripad et al, 2018 ; Tancred et al, 2017 ). Again, Site C illustrates this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of organizations are also more motivated when their environments are conducive to success ( Dekker, 2008 ; de Kok et al, 2020 ; Julien et al, 2021 ; Mathauer & Imhoff, 2006 ; Sripad et al, 2018 ; Tancred et al, 2017 ). Again, Site C illustrates this.…”
Section: Discussionmentioning
confidence: 99%
“…It remains, therefore, an open question how widespread the organizational cultures we describe are, and the findings presented here are facility-level cases which should not be taken to represent Malawi’s MoH as a whole. The conditions in the facilities described here are not unique within Malawi ( de Kok et al, 2020 ), or sub-Saharan Africa ( Julien et al, 2021 ; Sripad et al, 2018 ; Tancred et al, 2017 ), however, and it may be worth expanding future studies to generate data suitable for investigating organizational culture formation and change processes.…”
Section: Discussionmentioning
confidence: 99%
“…Other work in the Agincourt HDSS has shown a need for additional training on HIV treatment as prevention, 31 and providers discussed a need for trainings in skills and new treatment guidelines. 34 The current training model, where one senior staff member is sent to a training and then expected to disseminate information to the rest of the staff, does not appear to meet providers’ needs. Sending a master trainer to provide in-service trainings in the clinics themselves could be a viable option to address the challenge of knowledge dissemination without taking providers away from their facilities.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Other research has found poor hygiene and infection control in South African healthcare facilities. 2 , 19 , 34 Structural issues noted by providers such as leaking roofs, collapsed ceilings, insect and bat infestations, all require immediate attention and maintenance to ensure safe environments for providers and patients. One provider felt the poor infrastructure was indicative of the South African government’s lack of attention to rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…While patient-centered care focuses on the patient’s needs and preferences, it is important to keep in mind that managing infertility cases can be emotionally draining for physicians, as was described by some participants in our study. This can be exacerbated when paired with a high workload and stressful work environment, which studies in Ghana and South Africa have found can negatively impact physicians’ attitude toward patients and their ability to provide quality care (Avortri & Modiba, 2018; Julien et al, 2021; Rominski et al, 2017). More research is needed to understand how deficiencies in system factors impact physicians’ attitudes and their ability to provide patient-centered care for those with infertility.…”
Section: Discussionmentioning
confidence: 99%